M143 Progression Of Central Arterial Stiffness In Copd After 2 Years Of Observation. (10th November 2014) - Gale, NS; Albarrati, AM; Munnery, MM; Munnery, IC; Tal-Singer, RM; Cockcroft, JR; Shale, DJ
Abstract : Background: COPD is a systemic disease with associated comorbidities including cardiovascular disease which have significant impact on morbidity and mortality. The heterogeneity of COPD has led to the concept of phenotypes; one of which may describe patients at greater cardiovascular risk. Aortic pulse wave velocity (aPWV) is a validated measure of arterial stiffness and an independent predictor of cardiovascular outcomes, and has been shown to be elevated in patients with COPD. 1 We hypothesised that a subgroup of patients (progressors) would demonstrate increased aPWV over 2 years. Methods: The ARCADE study is a longitudinal study of cardiovascular risk and other comorbidities. Assessments include spirometry, BMI, aPWV and blood pressure, (BP), mean arterial pressure (MAP), heart rate and 6 min walk distance (6MWT). Based on the change in PWV in hypertensive patients, progressors were defined as individuals with >0.5 m/s PWV increase, over 2 years. 2 Results: Thus far 200 patients with COPD have completed the 2 year follow-up assessment. At baseline the progressor and non-progressor were similar in age, gender, BMI, heart rate and 6 MWT. However the progressors had greater airways obstruction, and lower mean arterial pressure and aPWV (Table 1 ). After 2 years the mean [95% CI] PWV change in progressors was +1.7 [2.0–1.5]m/s while FEV1 declined by 140 [76–206]ml (p < 0.05). In contrast the non-progressors had no change in lung function, while there was a decrease in aPWV 0.7 [0.5–0.9] m/s and MAP 5 [3–7] mmHg (p < 0.05). Conclusions: Almost half of the ARCADE subjects with COPD had a significant increase of PWV, the clinical relevance requires investigation using longer-term outcome data. The identification of CV risk phenotypes in COPD and the underlying pathophysiology may help identify novel therapeutic targets and improve CV outcomes for patients. Thank you to all our volunteers and GlaxoSmithKline who funded ARCADE NCT01656421 References: Sabit, R., et al ., AJRCCM, 2007. 175(12): p. 1259-1265 Benetos, A., et al ., Circulation, 2002. 105(10): p. 1202-1207